THE EFFECT OF FINANCIAL LITERACY, SELF-EFFICACY ON RISK CREDIT BEHAVIOR AMONG STUDENTS OF THE UNIVERSITY OF MUHAMMADIYAH SURAKARTA - Lestari, Niya Langgeng; Imronudin, Imronudin (Dynamic Management Journal, 2024)
This study aims to determine the effect of financial literacy, self-efficacy on risky credit behavior among students of Universitas Muhammadiyah Surakarta. The research method was carried out using a quantitative method with a sample of 150 respondents. The analysis of the research test used SmartTPLS. The results of the study showed that financial literacy had a positive impact on their risky credit behavior. In addition, selfefficacy mediates financial literacy's effect on risky credit behavior